1991
DOI: 10.1111/j.1476-5381.1991.tb12409.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity analysis of binding kinetics for NMDA receptor competitive antagonists: the influence of conformational restriction

Abstract: 1 The kinetics of action of 17 structurally related NMDA receptor competitive antagonists were measured under voltage clamp in mouse hippocampal neurones. Analysis of the response to rapid changes in antagonist concentration during constant application of agonist was used to estimate microscopic association (k0.) and dissociation (k0ff) rate constants for antagonist binding, assuming a two-equivalent site model for competitive antagonism. Dose-inhibition curves were analysed to estimate antagonist equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Thus in our simulation, we have assumed an association rate (k ϩB ) for NVP-AAM077 at both NR2A and NR2B subunits of 1 ϫ 10 7 M Ϫ1 s Ϫ1 . Such a value is consistent with published values for this parameter obtained from studies that have examined a variety of competitive antagonists at NMDA receptors (Benveniste et al, 1990;Benveniste and Mayer, 1991). Thus, to agree with our K B values, we fixed the dissociation rate constants (k ϪB ) for NVP-AAM077 at 0.15 and 0.78 s Ϫ1 for NR1/NR2A and NR1/NR2B NMDA receptors, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Thus in our simulation, we have assumed an association rate (k ϩB ) for NVP-AAM077 at both NR2A and NR2B subunits of 1 ϫ 10 7 M Ϫ1 s Ϫ1 . Such a value is consistent with published values for this parameter obtained from studies that have examined a variety of competitive antagonists at NMDA receptors (Benveniste et al, 1990;Benveniste and Mayer, 1991). Thus, to agree with our K B values, we fixed the dissociation rate constants (k ϪB ) for NVP-AAM077 at 0.15 and 0.78 s Ϫ1 for NR1/NR2A and NR1/NR2B NMDA receptors, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…However, the biochemical and functional studies reported to date are ambiguous with regard to NMDA receptor subunit stoichiometry. Functional studies indicate that binding of at least two molecules of both glutamate and glycine is required for NMDA receptor activation, suggesting that at least four subunits must co-assemble (11)(12)(13). The molecular size of native NMDA receptors, as determined by both gel filtration and native polyacrylamide gel electrophoresis, is in the range of 605-850 kDa, which is consistent with the coassembly of between four to five subunits (14 -16).…”
supporting
confidence: 54%
“…3A; see Table S2 for rate constants), the receptor contains two equivalent glutamate binding sites (i.e., GluN2 subunits) and requires agonist occupancy at both of these sites for activation. We assume that the association rate (k +B ) of the antagonist ST3 is 10 μM −1 ·s −1 , consistent with values for other competitive NMDA receptor antagonists (28,29). The antagonist dissociation rates (k -B ) for ST3 are therefore 0.52 s −1 at GluN1/2A and 7.8 s −1 at GluN1/2B, according to the experimentally determined…”
Section: Significancementioning
confidence: 92%
“…The presence of competitive antagonist will reduce the fraction of NMDA receptors that activate during synaptic release of glutamate. That is, the antagonist will bind a subset of NMDA receptors, depending on antagonist concentration and binding affinity, and prevent agonist binding and subsequent gating of these receptors after synaptic release of glutamate; the mean lifetimes of antagonist-receptor complexes are typically much longer than the few milliseconds that glutamate is available for binding (28,29). Frizelle et al (15) used kinetic modeling to predict that, under nonequilibrium conditions relevant to those encountered during rapid release and removal of synaptic glutamate, NVP is incapable of fully inhibiting Glutamate concentration-response data in the absence or presence of antagonist were analyzed by simultaneously fitting all data to both the Schild and Hill equations using global nonlinear regression (SI Materials and Methods).…”
Section: Significancementioning
confidence: 99%